(untitled) (Global Journal of Management and Business Research, 2013)
The objectives of this article are to: (1) define the audit interference rule (hereinafter "A.I.R.") and describe its purpose; (2) summarize the historical case law pertinent to the A.I.R.; (3) delineate the U.S. states that recognize the A.I.R. from those that do not; (4) explain how the A.I.R. is impacted by the existence of a state’s comparative negligence statute; and (5) tell how recent developments in case law are affecting the A.I.R. The purpose of the A.I.R. is to limit the scope of an auditor’s contributory negligence defense in a negligence lawsuit filed by a client. The A.I.R. provides that the client’s negligence is a defense only when it has contributed to the accountant’s failure to perform his contract and to report the truth. New York was the first state to recognize the A.I.R.